Efeito da temperatura de calcinação de argilas vermelhas na atividade pozolânica de cimento Portland - Oliveira, Américo Bertulino de (2019)
Pozzolans as a component material in the production of concrete and mortar is an issue of historical basis since Greeks and Romans have already used this material in their constructions. Nowadays, the demands of engineering and the interest in mitigating some environment effects caused by the extraction of resources and their impacts, the research centers have been engaged in searching new materials or materials with less impact to the environment, and pozzolans are among these materials. The replacement of part of cement for pozzolans is widely used because it gives to the cement some qualities and soothes some effects to the environment. From this current dynamic, this work proposed the calcination of clay in natura at different temperatures of 600 °C, 700 °C, 800 °C, 900 °C and 1000 °C. In an oven with controlled heating ramp at 45 °C/min to produce calcined clay and to measure its pozzolanicity potentials in Portland cement mortar as well as its compressive strength at 7, 28 and 90 days of ripening. Materials were characterized by TG, DTA, FRX and DRX; in addition to physical tests such as specific masses, laser granulometry, and the pozzolanic activity index of each calcined pozzolan. It was used for data analysis, the Tukey test statistical tool to find the sample with the greatest significance in relation to the 288 molded bodies. The work was carried out at the laboratories of UFPB and IFPB, where the clay was prepared by destroying it, followed by grinding in a disk mill to improve its contact surface with oven atmosphere, after calcination was ground in a ball mill at 8,500 cycles at their maximum load; the fineness of the masses was measured by laser granulometry, the bodies were molded with CP-V cement, cured in time and rupture to compression. On each rupture date, the DRX of the material was made. At each rupture date the material was DRX. The results showed us that as the temperature increased the material fineness increased, and that all material passed 100% in the # 75 μm mesh sieve; In X-ray diffractograms the calcium hydroxide (portlandite) peaks almost disappeared at 90 days, implying their consumption due to the pozzolanic effect and the presence of amorphous material. The simple compressive strengths showed evolution and a significant increase from 28 days, as well as interesting improvements and advances at 90 days, such as pozzolans at 1000 ° C with 30% surpassing the reference with 0% and resembling, in module, to the results of high performance mortars.